Catalyst–Electrolyte Interactions in Aqueous Reline Solutions for Highly Selective Electrochemical CO2 Reduction. Issue 2 (6th November 2019) - Garg, Sahil; Li, Mengran; Rufford, Thomas E.; Ge, Lei; Rudolph, Victor; Knibbe, Ruth; Konarova, Muxina; Wang, Geoff G. X.
Abstract: Achieving high product selectivities is one challenge that limits viability of electrochemical CO2 reduction (CO2 R) to chemical feedstocks. Here, it was demonstrated how interactions between Ag foil cathodes and reline (choline chloride + urea) led to highly selective CO2 R to CO with a faradaic efficiency of (96±8) % in 50 wt % aqueous reline at −0.884 V vs. the reversible hydrogen electrode (RHE), which is a 1.5‐fold improvement over CO2 R in KHCO3 . In reline the Ag foil was roughened by (i) dissolution of oxide layers followed by (ii) electrodeposition of Ag nanoparticles back on cathode. This surface restructuring exposed low‐coordinated Ag atoms, and subsequent adsorption of choline ions and urea at the catalyst surface limited proton availability in the double layer and stabilized key intermediates such as *COOH. These approaches could potentially be extended to other electrocatalytic metals and lower‐viscosity deep eutectic solvents to achieve higher‐current‐density CO2 R in continuous‐flow cell electrolyzers. Abstract : Interactive electrocatalyst : Excellent performance of electrochemical CO2 reduction results from reline‐induced surface interactions that restructured the Ag surface as well as the specific adsorption of choline ions and urea on the electrode surface.